Estudo teórico da fotoquímica do 1-cloro-1-flúor-metano (HCFC-31) - Silva, Albert Jorgivan Filho Wesley Hess de Sousa (2019)
Some of the compounds that are directly linked to the problems of consumption of atmospheric ozone and global warming are hydrochlorofluorocarbons (HCFCs), species consisting of hydrogen, carbon, fluorine and chlorine. The chlorine radical (Cl•) from photochemical reactions of HCFCs is one of the main causes of O3 reduction. This work consists of a theoretical study of the photochemistry of 1-chloro-1-fluoro-methane, H2CFCl (HCFC-31), using highly correlated methods such as multi-configurational SCF (MCSCF) and MR-CISD and MR-CISD+Q multi-references. The choice of the active space of the radical H2CF• was found by comparison with the literature based on the energies of vertical excitation and the valence and Rydberg states. The obtaining of the adequate set of active orbitals of H2CFCl and the number of states started from the active space and the number of states of the radical H2CF•, in which a CAS (10.7) and 19 states were obtained. The potential energy curves were mapped and their states were characterized. The ionic state (IS), corresponding to the couple H2CF+ (1A ') / Cl- (1S), was found and presented high moment of dipole (μ = 9.635 D) and separation of charges of Mulliken ( = 0.72), corresponding to the ionic complex FHC+H∙∙∙Cl-. The formation of this state is favored over the other states that lead to the release of the chlorine radical by having an intramolecular hydrogen bond H···Cl, with a binding energy of 4.34 eV